Time Management Strategies for Chairs and Administrators - Gian S Pagnucci; Ethan Krase (Academic Chairpersons Conference Proceedings, 2015)
This session will introduce department chairpersons and other administrators to a variety of time-management techniques for helping perform one’s job more effectively. The presentation will cover time management philosophies and practical strategies. Attendees will leave with new ideas for how to manage tasks more effectively and thereby reduce stress levels.
Keywords: time management; task management; stress reduction; productivity; email management